Method of Video-Measurements of Traffic Flow Characteristics at a Road Junction - Marina Yashina; Maria Belova; Alexey Mokhov (Journal of Information Technology Management)
In the theory of traffic flows the main characteristics are: intensity, speed, and density.  They make it possible to use hydrodynamic models. In connection with the development of modern highways and road networks, traffic flows behavior is becoming more and more complex and diverse. In particular, the B.Kerner studies have shown that the laminar solution of hydrodynamic models is poorly correlated with experimental data. Our research team is developing tools for intelligent monitoring of traffic flows on fragments of the road network with different geometries.  The paper presents a project of a client-server system, which allows obtaining, in real-time, information regarding the basic characteristics of traffic flows at the junction of any configuration using mobile devices. The automation of obtaining characteristics is based on the application of image recognition algorithms (virtual detection method).